2022
DOI: 10.1155/2022/3170947
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Caffeine Intake on Cardiopulmonary Variables and QT Interval after a Moderate-Intensity Aerobic Exercise in Healthy Adults: A Randomized Controlled Trial

Abstract: Caffeine is considered a widely consumed natural and legal psychoactive stimulant with several effects on the body. The present study attempted to investigate the effects of caffeine consumed before and after a physical exercise on cardiovascular and cardiorespiratory functions in healthy adults. 36 healthy adult males were recruited and randomly allocated to one of the three (3) groups: group I (exercise without caffeine consumption), group II (caffeine beverage intake before exercise), and group III (caffein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Stadheim et al ( 65 ) found that caffeine enhances the activity of the sympathetic nervous system, causing an increase in HR. In contrast, other studies have shown that oral caffeine can lower HR during exercise ( 66 , 67 ). Other studies have also shown that caffeine did not affect HR when the participants exercised at 33 ° C or 37 ° C ( 68 , 69 ), which was consistent with our findings.…”
Section: Discussionmentioning
confidence: 76%
“…Stadheim et al ( 65 ) found that caffeine enhances the activity of the sympathetic nervous system, causing an increase in HR. In contrast, other studies have shown that oral caffeine can lower HR during exercise ( 66 , 67 ). Other studies have also shown that caffeine did not affect HR when the participants exercised at 33 ° C or 37 ° C ( 68 , 69 ), which was consistent with our findings.…”
Section: Discussionmentioning
confidence: 76%
“…(Ruíz-Moreno et al, 2020) Ainda, podemos afirmar que a ingestão de cafeína antes e após exercício aeróbico moderado retarda a estimulação parassimpática, a recuperação da frequência cardíaca e a recuperação da FC e QTc sem maiores efeitos na PA, FR, VO₂ e VCO₂ em homens adultos saudáveis. (Yu et al, 2022) O estudo com atletas do município de Macaé, demonstrou que usuários classificados como consumidores baixos níveis de cafeína conseguiram atingir a faixa ergogênica expressivas por meio do consumo de fontes alimentares, sem o uso de suplementos. Revelando que pequenas doses já são perceptíveis na melhora dos níveis de desempenho durante a prática de esportes.…”
Section: Ruíz-moreno Et Al (2020)unclassified
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%